(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article studies the kinetic properties of the reactions of alkali metals (lithium, sodium, potassium, etc.) with water and various chemical reagents. The study analyzes the rate of reactions, the temperature affecting them (concentration, nature of the metallurgy, and surface area).